Waste: awareness and responsibility / Marlina Mohd Mydin and Siti Suhaila Harith - Mohd Mydin, Marlina; Harith, Siti Suhaila (2015)
Urbanization and population growth had generally increased the standard of living in Malaysia which also increase the waste generation. The main purposes of the study are to gather information regarding the composition of waste produced from the entire campus of UiTM Pahang and to develop a representative estimation of the university's solid waste stream. This study was carried out for three months in 2014. The waste was collected from three different sites in UiTM Pahang. The wastes were segregated to eight different categories and the weight was recorded. The solid waste composition showed that the major contributor to the total waste output in UiTM Pahang was from commercial sites about 37% followed by domestic 36% and office 27%. On the other hand, the largest proportion of solid waste by percentage is contributed by putrescible waste (30%). This is followed by paper (20%), plastic (10%) and metal (5%). In conclusion, the wastes from UiTM Pahang are highly biodegradable and place a great potential for recycling. Regardless of the type of recyclable materials, the awareness toward waste recycling is poor and most individuals are not able to translate their concerns to act upon the matter.